An Analysis of Humor Translation Techniques and Quality in the English Translating Subtitles of Indonesian Comedy Film Agak Laen (2024) (English Language and Literature (JELL), 2026)
This study analyzes the translation of humor in the English subtitles of the Indonesian comedy film Agak Laen (2024). Humor, as a complex linguistic and cultural element, presents significant challenges in audiovisual translation due to the heavy use of regional dialects and cultural-specific references. This research aims to identify the translation techniques used and to assess the quality of the translation in terms of accuracy and acceptability. Using a descriptive qualitative method, data were collected through document analysis of humorous utterances in the film. The analysis applies Molina and Albir's (2002) translation techniques and Nababan's (2012) translation quality assessment. The findings reveal that Reduction is the most dominant technique used by the translator, accounting for 18.03% of the total techniques applied, followed by Literal Translation (16.39%) and Discursive Creation (15.3%). Regarding translation quality, the results show an average score of 2.40 for accuracy, categorizing it as Less Accurate, and 2.52 for acceptability, categorizing it as Acceptable. The lower accuracy score is primarily attributed to the frequent use of reduction and literal translation for cultural terms and wordplay, which often results in a loss of specific humorous nuances and slight meaning distortion in the target language.
Keywords: Humor translation, Translation Techniques, Translation Quality, Subtitles, Agak Laen Film